BUTLER, J. (2021). Excitable Speech. A Politics of the Performative. Nueva York: Routledge - Moscoso Cala, Javier (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: BUTLER, Judith, (2021), Excitable Speech. A Politics of the Performative, Nueva York, Routledge.